Alkaloids: Chemical and Biological Perspectives - Pelletier, S. William (New York, NY : Springer New York, 1991)
This monograph series provides unprecedented interdisciplinary coverage of research relating to the chemistry and biology of alkaloids - a class of biologically active compounds of more than 10,000 members. Timely, comprehensive and authoritative, the series features chapters on chemical properties and structure elucidation, synthesis, biosynthesis, taxonomy, spectroscopy, pharmacology, and toxicology. These vol- umes will provide valuable information for investigators working in such diverse fields as medical chemistry, natural products chemistry, pharmacology, pharmacognosy, physiology, biochemistry, phytochemistry, plant taxonomy, oncology, forensic science, and medicine. The chapters are written by eminent researchers, all of them acknowledged experts in the field. Subject and organism indexes are included.
Homoerythrina and Related Alkaloids -- Carbon-13 NMR Spectroscopy of Steroidal Alkaloids -- Carbon-13 and Proton NMR Shift Assignments and Physical Constants of Norditerpenoid Alkaloids -- Subject Index -- Organism Index.
Keywords: Chemistry; Chemistry, Organic; Electronic books